1997
DOI: 10.1097/00006842-199711000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors in Fibromyalgia Compared With Rheumatoid Arthritis

Abstract: Despite the absence of organic pathology, the patients with fibromyalgia had equal or greater functional disability and were less well adapted to their illness. Although the pathophysiology of fibromyalgia remains unclear, co-morbid psychiatric disorders and functional disability remain an important focus of treatment in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
205
2
21

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(253 citation statements)
references
References 27 publications
25
205
2
21
Order By: Relevance
“…The large difference in perceived stress provides strong support that FM is 'stress-related' with regard to the current perception and experience of stress. In addition, the larger effects sizes for child and adult abuse as compared with other traumatic events is consistent with past research regarding the importance of relationship abuse and interpersonal stress in FM (Davis et al, 2001;Walker et al, 1997;Zautra et al, 1999).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The large difference in perceived stress provides strong support that FM is 'stress-related' with regard to the current perception and experience of stress. In addition, the larger effects sizes for child and adult abuse as compared with other traumatic events is consistent with past research regarding the importance of relationship abuse and interpersonal stress in FM (Davis et al, 2001;Walker et al, 1997;Zautra et al, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…There is increasing evidence that the ongoing perception of stress may be related to health in women with FM (Murray, Murray, & Daniels, 2006;Van Houdenhove et al, 2002;Zautra, Hamilton, & Burke, 1999). In addition, women with FM may have experienced more traumatic events than healthy women or women with other rheumatological disorders (Van Houdenhove et al, 2001;Walker et al, 1997) These higher levels of traumatic events and perceptions of stress are important because they have consistently been linked to worse health and lower well-being. Traumatic events such as motor vehicle accidents, sexual assault and natural disasters have been linked to increased anxiety, depression and post-traumatic stress disorder (Breslau et al, 1998;Grant, Beck, Marques, Palyo, & Clapp, 2008;Smith & Freedy, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual abuse, violence, the threat or the witnessing of either, which have been mentioned in some of our respondents have also been described as causes of psychological trauma. Other authors found a high prevalence (> 30%) of sexual and physical abuse in women with FM and reported higher rates of abuse in these patients as compared with a group of women without FM [45][46][47]. However, still other authors questioned the association between sexual abuse and FM onset [48][49][50].…”
Section: Discussionmentioning
confidence: 99%